Improving Mental Well-Being and Productivity of Small-Medium Entrepreneurs in Fragile, Conflict and Violence Affected Areas : Can Cognitive Behavioral Therapy Training Help? - Saraf, Priyam; Rahman, Tasmia; Gallardo, Miguel; Jamison, Julian; Lor, Charles (World Bank, Washington, DC, 2018)
This literature review summarizes the link between psychological well-being and entrepreneurial outcomes for small and medium-size enterprises in fragile, conflict, and violence–affected contexts. It identifies potentially promising, scalable psychosocial training interventions, based on cognitive-behavioral therapy approaches, that can be adapted and implemented to improve psychological health at the individual level, that could lead to better business performance at the firm level. The findings from the literature of cognitive psychology and small business economics suggest that small and medium-size enterprise entrepreneurs, without diversified capital, stable sources of income, or delegation opportunities, tend to suffer from more stress and anxiety compared with their peers in salaried jobs or in larger firms. Chronic stress is found to deplete their psychological resources, erode their motivating role within the firm, and result in counterproductive work behavior. The combination of regular business-related entrepreneurial stressors with the uncertainties of a fragile, conflict, and violence–specific environment—natural disasters, conflict, migration, and/or exposure to trauma—can amplify poorer psychological outcomes and hamper business performance. Utilization of cognitive-behavioral therapy approaches to mitigate stress and build psychological capital appears promising. Although such curricula have been tried and tested for other target groups at scale, such an intervention has not yet been applied for at-risk entrepreneurs. Given that small and medium-size enterprises are important drivers of income in fragile, conflict, and violence–affected contexts, future research might benefit from evaluating whether the effects of cognitive-behavioral therapy–based training interventions can be replicated for these new target groups and, importantly, whether the interventions can lead to better behavioral outcomes and business performance over time.